PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU BERBASIS ENTREPREUNER DI SMP N 1 SINGOROJO - Kuncoro Pujiwarto; Ngurah Ayu Nyoman; Endang Wuryandini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine: The objectives to be achieved in this study are to: a. Analyzing the role of the principal as a manager in improving teacher performance based on entrepreneurship at SMP Negeri 1 Singorojo, b. Analyzing the role of the principal as a supervisor in improving teacher performance based on entrepreneurship at SMP Negeri 1 Singorojo. This research is a type of research with a qualitative approach. The informants of this study were the principal as the research subject, vice principal, teachers, students and committee members of SMP N 1 Singorojo. Data collection techniques used interviews, observation and documentation, while data analysis techniques used Data Condensation. The results of the research show that: a. Principals can create an atmosphere of creative performance by coming up with innovative ideas through digital-based learning programs according to the stated vision, namely; "Creating quality cultured intelligent schools with digital services", teachers are motivated to be creative. B. The principal carries out collaborative supervision using the Office 365 Learning Management System (LMS), stimulating teachers to improve their performance. This thesis recommends for; A. Emphasizing the scientific aspect in the context of scientific development of the Principal's leadership. B. Become input for education providers who implement quality public services through improving teacher performance and Principal Competence. c. Being input and consideration for school principals in improving the performance of the teachers they lead, and motivating creative and innovative teacher work.